Modelo de gestão ambiental: estudo de caso em triparia no sudoeste do Paraná - Martini, Cezar Augusto (2012)
The worsening environmental and social problems represents a framework of unsustainability of the current standard of development, therefore, the companies must adopt instruments of environmental management as an alternative in search of sustainability. This study provides an application of a model of environmental management for gut sectors implanted in the southwest Paraná, seeking to increase the level of environmental sustainability of the company. Initially it was carried out the characterization of the company, producing descriptions and flowcharts activities, including industrial process, water treatment plants and liquid effluents, steam generation and solid waste, fleet of identification of environmental aspects of each activity, allowing the environmental analysis of the company, qualitatively and quatitatively, confronting the current situation with the environmental legislation, when applicable. In the next step, by applying a management tool, was carried out the assessment of environmental impacts, which includes the identification and assessment of the impacts. In conclusion, negative impacts were identified, particularly related to biological and physical environment, that can be minimized by the implementation of the programs and measures suggested, among them reduction in water consumption, reuse of effluent and rainwater, optimization of the treatment of effluents, adjust in the combustion process, regularization of legal non-conformities. On the other hand were identified positive impacts, particularly related to the socio-economic environment, that must be kept or extended, in order to allow the company to increase its level of environmental sustainability.